3D printed energy harvesters for railway bridges-Design optimisation. (1st May 2023) - Cámara-Molina, J.C.; Moliner, E.; Martínez-Rodrigo, M.D.; Connolly, D.P.; Yurchenko, D.; Galvín, P.; Romero, A.
Abstract: This paper investigates the optimal design of 3D printed energy harvesters for railway bridges. The type of harvester studied is a cantilever bimorph beam with a mass at the tip and a load resistance. These parameters are adjusted to find the optimal design that tunes the harvester to the fundamental frequency of the bridge. An analytical model based on a variational formulation to represent the electromechanical behaviour of the device is presented. The optimisation problem is solved using a genetic algorithm with constraints of geometry and structural integrity. The proposed procedure is implemented in the design and manufacture of an energy harvesting device for a railway bridge on an in-service high-speed line. To do so, first the methodology is validated experimentally under laboratory conditions and shown to offer strong performance. Next the in-situ railway bridge is instrumented using accelerometers and the results used to evaluate energy harvesting performance. The results show the energy harvested in a time window of three and a half hours (20 train passages) is E = 109 . 32 mJ . The proposed methodology is particularly useful for bridges with fundamental mode shapes above 4 . 5 Hz, however optimal design curves are also presented for the most common railway bridges found in practice. A novelty of this work is the use of additive manufacturing to 3D print energy harvesters, thus maximising design flexibility and energy performance. Highlights: Design optimisation of 3D printed energy harvesters for railway bridges is presented. Optimal design is obtained using a genetic algorithm with constraints. The methodology is experimentally validated for a railway bridge in-service. Energy in three and a half hours and 20 train passages could be higher than 100 mJ. Design curves are presented for most common railway bridges found in practice.